Antithrombotic therapy in antiphospholipid syndrome with arterial thrombosis: a systematic review and network meta-analysis - Attachaipanich, Tanawat; Aungsusiripong, Aimpat; Piriyakhuntorn, Pokpong; Hantrakool, Sasinee; Rattarittamrong, Ekarat; Rattanathammethee, Thanawat; Tantiworawit, Adisak; Norasetthada, Lalita; Chai-Adisaksopha, Chatree (Frontiers in Medicine, 2023)
The appropriate secondary thromboprophylactic strategies for Antiphospholipid syndrome (APS) with arterial thrombosis remain controversial. This study aimed to assess the relative efficacy and safety of antithrombotic strategies in APS with arterial thrombosis. We searched OVID MEDLINE, EMBASE, Web of Science, and the Cochrane Controlled Register of Trials (CENTRAL) from inception to September 30, 2022, without language restrictions. Eligible studies were those that (1) included APS patients with arterial thrombosis, (2) treated patients with either antiplatelet, warfarin, direct oral anticoagulants (DOACs), or a combination of these treatments, and (3) reported recurrent thrombotic events. A frequentist random-effects network meta-analysis (NMA) was conducted on thirteen studies comprising 719 participants, including six randomized and seven non-randomized studies. Compared to single antiplatelet therapy (SAPT), combined antiplatelet and warfarin was associated with a significantly lower risk of recurrent overall thrombosis, with a risk ratio (RR) of 0.41 (95%CI 0.20 to 0.85). Dual antiplatelet therapy (DAPT) was associated with a lower risk of recurrent arterial thrombosis compared to SAPT, but without statistical significance, with an RR of 0.29 (95%CI 0.08 to 1.07). However, the number of participants recieving DAPT treatment was limited in the included studies. DOACs were found to significantly increased the risk of recurrent arterial thrombosis, with an RR of 4.06 (95%CI 1.33 to 12.40) compared to SAPT. There was no significant difference in major bleeding among antithrombotic strategies. This NMA suggests that a combination of warfarin and antiplatelet therapy is an effective antithrombotic strategy in preventing recurrent overall thrombosis in APS patients with previous arterial thrombosis. DAPT may also be an effective treatment to preventing recurrent arterial thrombosis, but further studies are necessary to confirm its effectiveness. In contrast, DOACs were found to significantly increase the risk of recurrent arterial thrombosis.